2009
DOI: 10.21608/jacb.2009.90281
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizers and Their Importance in Environmental and Sustainable Agriculture

Abstract: The use of biofertilizers has become a great hope for Egyptian agriculture, particularly in the field of production of medicinal plants, especially when the economic and environmental points of view are considered, since they reduce the environmental pollution and production costs, in addition to improving the quality. Therefore, the influence of using locally isolated nitrogen fixing bacteria as biofertilizers were studied. The isolates used were three representative strains of either Azotobacter and Azospiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…Moreover, it produced some photohormones such as indole acetic acid, gibberellins and cytokinins, as well as, antibacterial substances which is vital (Hauwka, 2000). Our results were similar to those reported by Abdallah et al (2012) and Shehata (2019) The recent study showed that SE as well as Vit. B1 significantly increased almost all assessed traits compared with that of tap water treated plant on both seasons.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, it produced some photohormones such as indole acetic acid, gibberellins and cytokinins, as well as, antibacterial substances which is vital (Hauwka, 2000). Our results were similar to those reported by Abdallah et al (2012) and Shehata (2019) The recent study showed that SE as well as Vit. B1 significantly increased almost all assessed traits compared with that of tap water treated plant on both seasons.…”
Section: Discussionsupporting
confidence: 93%
“…Biofertilizers are one of these bio-stimulants which afford an economically cheap and ecologically safe fertilizer moreover, they are vital for sustainable agriculture by reducing the doses of chemical fertilizers (Chatterjee et al, 2017). Minia azotein (MA) (N-fixing biofertilizer) as a bio-stimulant has been applied to reduce mineral N fertilizer of different herbs (Abdallah et al, 2012) and (Shehata, 2019) on parsley; (Abdou et al, 2020) on fennel and (El-Sayed et al, 2020) on dill.…”
Section: Introductionmentioning
confidence: 99%